Publishing the Ghana Library Journal: Trends, Challenges and the Way Forward - Antwi, I.K. (Ghana Library Journal, 2006)
Journals provide current and up to date information, which in turn promotes teaching, learning, and research in addition to knowledge dissemination. Major professional associations therefore consider publishing journals as one of their core functions. It is therefore worthy of note that the Ghana Library Association (GLA) has since its formation been publishing the Ghana Library Journal (GLJ). This paper documents and discusses the experience of the GLJ since its inception in 1963 from the management perspective. The role of the GLA as the publisher, the Editorial Board, the Editor-in-Chief and even the role of members of the Association in ensuring its sustainability are highlighted. It also examines the constraints and challenges facing the continuous publication of the journal.The paper ends with a number of recommendations. These include expanding the financial base of the journal, effectively marketing the journal and also empowering prospective authors through workshops and seminars on writing and research skills.